Impact of Some Hormone Combinations on Feed Utilization, RNA/DNA Ratio, Enzyme Activity, Growth and Survival of Pearlspot, Etroplus suratensis (Bloch) - C., Sambhu; V., Jayaprakas (Fishery Technology, 2025)
Juveniles of pearlspot were reared by feeding diets enriched with steroid and protein hormone combinations: Testosterone propionate (TP), Diethyl stilbestrol (DES) and Human chorionic gonadotropin (HCG) at various doses for a period of 120 days and their growth performance was evaluated. The dosages of the hormone combinations were TP 2.0 ppm+DES 1.0 ppm (Tj), TP 2.0 ppm+HCG 5.0 ppm (T2), DES 1.0 ppm+HCG 5.0 ppm (T3) and TP 2.0 ppm+DES 1.0 ppm+HCG 5.0 ppm (T4). The fishes which received diets containing combinations of TP+HCG achieved the highest growth (40.10 g). Feed consumption, feed conversion efficiency and nutrient digestibility were higher in this group. Digestive enzyme activity was maximum (590.34 units/g tissue) in the intestine of fishes fed on diet containing TP+HCG. The RNA/DNA ratio and protein contents in the muscle increased concomitant with the high growth rate.